Ruthenium Carbonyl Compounds Containing Polypyridine Ligands as Catalysts in the Reaction of N-Benzylideneaniline Hydrogenation - Moya-Duran, S; Moya-Duran, S; Brown-Alvarez, K; Brown-Alvarez, K; Vidal-Palomo, M; Vidal-Palomo, M; Negrete-Vergara, C; Negrete-Vergara, C (2012)
Sin Editorial Disponible